Training System for Teacher Evaluation in Technical and Technological Training Institutions. A Playful Proposal - Parada-Romero, Laura (Revista Saberes Educativos, 2022)
To respond to the needs of an increasingly globalized world, it is urgent to guarantee the quality of education, a fundamental factor being the way in which teachers are evaluated, in particular those who work in technical and technological programs that allow the students to articulate with the labor sector. Teacher evaluation has been limited many times to the application of surveys to students, which has been questioned, since it is considered that it fails to evaluate objectively and adequately the abilities, capacities and qualities of teachers. In this research, an alternative to teacher evaluation, which involves play, is analyzed. Through a collaborative process between teachers and students, it results in the transformation of current realities, constituting a way to strengthen the training process.